Optimized selection of neodymium laser parameters for successful enlarged veins treatment - Mustafa, Muna B.; Hamoudi, Walid K.; Khashan, Khawla S. (Lasers in medical science, 2023)
Full clearance and no side effects method of treating enlarged veins was successfully accomplished by one laser session. This is the ambition and dream of both dermatologists and patients. Most vascularity treatment protocols had shown some unpleasant adverse effects. The purpose of the present work is to work out, in advance, the accurate dose of laser pulse duration and fluence in order to treat varicose veins in the face, arms and legs with no adverse effects. This mission required the calculation of the exact rise in temperature of the enlarged vein; prior to laser treatment. These pre-calculated temperature rise values were tested on 20 subjects in order to have the best clinical outcomes; using fundamental frequency (1064 nm) pulsed Nd: YAG laser. This work necessitated the use of pulse length (15–30 ms), spot size (3, 5 mm), fluence (110–190 J/cm 2 ) and skin cooling temperature (3–18 °C). Cooling of the skin before and after the treatment was needed to guarantee ultimate impactful results without side effects.